1993
DOI: 10.1007/bf00920945
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular extracellular cyclic nucleotide concentrations: the influence of vitreous surgery

Abstract: Levels of cAMP (23.1 pmol/ml) and cGMP (22.6 pmol/ml) are nearly equal in normal rabbit vitreous, although aqueous cAMP levels (29.9 pmol/ml) are 10 times higher than aqueous cGMP levels (2.6 pmol/ml) (P < 0.01). Intravitreal cAMP values decrease slightly 1 week after vitrectomy and lensectomy and return to normal whether the retina is attached, detached, or surgically removed. In contrast, intravitreal cGMP levels are profoundly depressed at 7 days (approximating normal aqueous levels) and are more than 50% l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…In normal rabbit eyes cGMP levels in aqueous humour were 10 times lower than in vitreous humour. 10 Despite a small extra amount of cGMP which may have been derived from the aqueous humour however, subretinal cGMP levels in the current study were even lower than vitreous cGMP levels.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In normal rabbit eyes cGMP levels in aqueous humour were 10 times lower than in vitreous humour. 10 Despite a small extra amount of cGMP which may have been derived from the aqueous humour however, subretinal cGMP levels in the current study were even lower than vitreous cGMP levels.…”
Section: Discussioncontrasting
confidence: 65%
“…Our study confirms earlier findings in a rabbit model with retinal detachment, 10 that showed that vitreous cGMP levels were almost 60% lower than in normal rabbit eyes without detachment. 10 Because we have not found previous studies on cGMP in normal or pathological human vitreous fluid or subretinal fluid in the literature (computerised search through Medline), we cannot compare our findings with studies in humans.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, corneal endothelium is constantly bathed in aqueous humor containing a high level of cAMP. 17 Thus, corneal endothelium is equally exposed to the opposite effectors that ultimately regulate the behavior of the cells. Therefore, we addressed whether cAMP directly affects FGF-2 activities.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Although FGF-2 is known to cause mitogenic activity under some pathologic conditions, human corneal endothelium in vivo remains arrested in the G 1 phase of the cell cycle, [11][12][13][14] but the mechanism of this arrest at G 1 is not known. Nevertheless, some researchers have proposed that TGF-␤2 and cAMP, the two resident components in the aqueous humor [15][16][17] in which CECs constantly bathe, play key roles in maintaining CECs in G 1 arrest in vivo and in vitro. 16, 18 We have reported that 8-bromoadenosine cAMP (8-Br-cAMP), a nonhydrolysable but diffusible cAMP analogue, inhibits serum-mediated cell proliferation in CECs by upregulating p27; in addition, 8-Br-cAMP blocks phosphorylation of p27, which is a prerequisite for nuclear export of p27 for degradation.…”
mentioning
confidence: 99%
“…1,2 Adult human corneal endothelial cells (CECs) are mitotically inactive, at least partly because of lack of mitogenic stimulation, 3 cell contact inhibition, and the presence of anti-mitogenic factors in the aqueous humor. 4,5 When the corneal endothelium is injured, the nearby normal CECs enlarge and migrate to fill the space resulting from loss of injured cells. 6,7 However, there is emerging evidence suggesting that CECs can undergo endotheliumto-mesenchymal transition (EnMT) after chemical, mechanical, or other injury.…”
mentioning
confidence: 99%